Perceptions and knowledge of school management teams about non-communicable diseases and strategies to prevent them - Sibusiso C. Nomatshila; Teke R. Apalata; Sikhumbuzo A. Mabunda (AOSIS, 2022)
Background: In 2016, non-communicable diseases (NCDs) were reported to be responsible for 41 million of the world's 57 million deaths. These deaths were reported to be associated with modifiable lifestyle behaviours, such as tobacco smoking, poor physical activity and diets of poor nutritional value. There could be a knowledge gap on NCD risk factors amongst non-health professionals. Knowledge of NCDs is, therefore, important for the implementation of preventive measures to onset of NCDs. Aim: This study aimed at describing perceptions and knowledge of school management teams about NCDs and strategies to prevent them. Setting: This study was conducted in Mt Frere, South Africa. Methods: This explorative qualitative study using a phenomenological data collection approach was conducted amongst purposively selected school authorities in 2016-2017 to understand their perceptions and knowledge about NCDs and what can be performed to prevent them. Two focus group discussions (FGDs) were conducted using open-ended and unstructured questions guided by interview schedule. Tesch's eight phases of thematic analysis approach was used to analyse narrative data resulting in two main themes and nine subthemes. Results: Two themes (understanding and prevention of NCDs, and control measures for NCDs) and nine sub-themes emerged from the data analysis. Inconsistent description of NCDs, its causes and controls were identified amongst school management teams in the FGD. Diet, poverty, societal factors, gaps between decision makers and communities, and poor policy implementation were identified by participants as major issues in the development of NCDs. Conclusion: There was no adequate knowledge on NCDs amongst the school management team participants. Improved visibility of health promotion personnel is needed to ensure community empowerment on NCDs prevention. Contribution: The findings in this study will help in closing the gaps in the implementation of preventive health services for NCDs within school health.